A CASE STUDY OF MULTIMODAL ANALYSIS: THE REPRESENTATION OF A FEMALE MODEL IN THE 'INSIGHT' RUBRIC OF MALE MAGAZINE 147TH EDITION - Sriratu, Vinakha Naraswas (2016)
The present study entitled "A Case Study of Multimodal Analysis: The Representation of a Female Model in the 'Insight' Rubric of Male Magazine 147th Edition" aims at discovering the image of Indonesian women presented in the men's magazine visually and verbally. Using a descriptive qualitative method, this study applies multimodality based on Halliday's (1994) Systemic Functional Linguistics to analyze the visual and verbal modes in the data. In the visual stage, the data are analyzed by Kress and van Leeuwen's (2006) visual grammar, Wilfred's (1962) meaning of colors, and Barnard's (2007) theory of fashion and physical appearance. Meanwhile, the verbal data are analyzed Halliday's (1994) transitivity. The findings show that the integrated visual and verbal modes complement each other to construct the image of the female model. The female model is visually represented as a physically and spiritually beautiful woman with aggressiveness. In addition, the female model is verbally represented as a hardworking, popular, and, curious woman who tends to use her feelings in life. Those representations can lead her to be the sex object for men yet powerful woman. In relation to the gender issue, the study concludes that the magazine reflects how women's stereotypes change overtime depending on the cultural society.; Studi yang berjudul "Studi Kasus Analisis Multimodal: Representasi Model Perempuan di Rubrik 'Insight' Majalah "Male" Edisi 147" ini bertujuan untuk mengetahui imej wanita Indonesia didalam majalah lelaki secara visual dan verbal. Dengan metode deskriptif kualitatif, studi ini mengaplikasikan multimodality yang berdasar pada teori Halliday (1994), Systemic Functional Linguistics, untuk menganalisa gambar dan tulisan pada data. Untuk gambar, data dianalisa menggunakan Visual Grammar oleh Kress dan van Leeuwen (2006), arti warna oleh Wilfred (1962), dan arti fashion dan penampilan fisik oleh Barnard (2007). Sementara, data tulisan dianalisa menggunakan transitivity oleh Halliday. Hasil menunjukkan bahwa mode visual dan verbal yang saling terhubung melengkapi satu sama lain untuk membangun imej model perempuan pada data. Model perempuan tersebut secara visual dapat direpresentasikan sebagai wanita agresif yang mempunyai fisik dan perilaku yang baik. Sebagai tambahan, model perempuan juga secara verbal direpresentasikan sebagai wanita pekerja keras, terkenal, dan sangat perasa. Seluruh representasi tersebut menjadikan ia sebagai wanita objek seksual untuk lelaki tetapi juga memiliki kekuatan. Dikaitkan dengan isu stereotip gender, studi ini menyimpulkan bahwa majalah "Male" merefleksikan bagaimana stereotip wanita berubah setiap waktu tergantung pada budaya suatu masyarakat.